A study on the effect of noise, correlated to test scores in reading comprehension test - Cada, Melissa S. (1999)
This study involved thirty-six UP Tacloban College students, who were randomly chosen from three chosen courses classes from UP Tacloban College, Tacloban City. These thirty-six (36) students were divided into three groups making one controlled group and two experimental groups. This research was conducted to examine whether the presence of noise or music has significant effects on reading comprehension test. Furthermore, if the respondents would finish the test in the time allotted, given that there is the presence of noise, they would be able to finish the test. For this reason, a research instrument was distributed, thus a standard reading comprehension test by the Flanagan Industrial Test (Form A) that is to be answered within fifteen minutes with twenty-six items and has four passages of reading selection to be read by the respondents. The controlled group was made to answer the test without the presence of noise while the two experimental groups were made to answer it with pleasant music and the other experimental group with the presence of noise that is the rock music. The researcher used 1x3 factorial design since there was one independent variable and three dependent variables, that is the reading comprehension test and the controlled group and two experimental groups. Results indicated that the performance of each group that is with the presence of noise, affect the ratings of the respondents such, that the controlled group has the highest rating compared to the two experimental groups had lower ratings because of the presence of noise.
Thesis Manuscript (B.A.S.S. Psychology) -- University of the Philippines, Tacloban.
Keywords: Social Science